Learning about English learners: teachers' and leaders' perceptions of effective professional development. Issue 2 (3rd April 2022) - Vera, Elizabeth M.; Heineke, Amy; Israel, Marla; Hill, Martin; Goldberger, Nancy; Hook, Kimberly; Anderson, Bernasha
ABSTRACT: Shortcomings in schools' efforts to serve English learners (ELs) are often both a function of the continuing scarcity of teacher education and the ability of schools to implement high-quality professional development (PD) to successfully prepare effective teachers for this marginalized student population. Scant literature addresses the processes for initiating EL-focused PD, as well as the effectiveness of PD at the school-wide level. In this study, survey data collected from designing and delivering PD were examined to ascertain what makes for effective PD with respect to teaching ELs. Results of this multi-phase study suggest that educators are looking for not only how they can assess and accommodate the learning needs of ELs but also how to better support the larger contexts in which they learn. Additional findings included the need for learning specific types of strategies, conceptual frameworks, and interventions to help ELs learn both literacy, as well as in specific content areas. Implications for designing and evaluating EL-focused PD are discussed.